India's progress on its climate action plan: An update in early 2022 - Mohua Mukherjee (The Oxford Institute for Energy Studies, 2022)
India has been implementing climate actions since 2001, when it was one of very few countries to pass an Energy Conservation Act, followed by an industrial emissions trading scheme to force large manufacturing companies to become more energy efficient. A National Action Plan for Climate Change (NAPCC) was passed in 2008, and included relatively modest solar energy targets (20 GW by 2022) along with seven other action areas. Prime Minister Modi, who took office in 2014, brought new momentum to the solar energy sector by raising ambition five-fold. Overnight, the original National Solar Mission target of 20 GW was increased to 100 GW. This ratcheting up of the target was to become the norm. India's growing renewable energy (RE) investment has been underpinned by consistently increasing the level of ambition announced to private investors, domestic and foreign. Progress on the ground has been remarkable, despite the last two years being disrupted by Covid 19-related restrictions. Installed solar PV capacity since 2014 has grown to 50 GW by February 2022, of which 43 GW are ground mounted and 7 GW are grid-connected rooftop PV. Overall installed renewables (solar, wind and biomass) stand at just over 100 GW. If large hydro is included, the currently installed total capacity rises to 150.9 GW. Around 53 GW of renewable investments are currently at various stages of preparation, contract award or construction. Current milestone targets call for 175 GW of renewables by 2022, and 500 GW by 2030, on the way to net zero in 2070. Today India has the world's fourth largest installed capacity of renewable energy and the fifth largest installed capacity of solar PV. In 2021, Solar PV accounted for 62% of new capacity addition, which was the largest share of capacity ever in India. Renewables overall accounted for 77% of new capacity addition in 2021. Apart from renewable energy capacity expansion, a number of landmark achievements have also taken place on the energy efficiency front, and these are presented in detail in the paper. In terms of the big picture, this paper also lays out and examines the conundrum facing India, in terms of the scope of the challenge and the balancing act it is trying to follow between meeting economic development goals and climate goals. Given its stage of development, India still has a huge unfinished economic growth and poverty alleviation agenda as it also simultaneously tackles the climate agenda, using its own budgetary resources. If India is able to find a pathway that succeeds in balancing all of the above, and meeting both Sustainable Development Goals and Climate Action Goals, then not only India, but the entire world, will be better off. What happens in India, doesn't stay only in India because India moves the global needle on climate action.
Keywords: 330; Climate Action; decarbonization; Efficiency; Energy Transition; India; Renewables